Gulf Economic Update, December 2019 : Economic Diversification for a Sustainable and Resilient GCC - World Bank (World Bank, Washington, DC, 2019)
This edition of the Gulf Economic Update explores the links between economic diversification and environmental sustainability. The analysis highlights the need to integrate environmental sustainability and ecosystem resilience considerations into the decision-making process on the diversification paths and options in the GCC countries.